The Role of Foreign Investors in Debt Market Development : Conceptual Frameworks and Policy Issues - Lee, Jeong Yeon (World Bank, Washington, DC, 2014)
To take full advantage of foreign investors, a host country must provide an appealing environment: a stable economic and political environment; a fair, rational, and, comprehensive legal system; a fair, reasonable, and, balanced tax program; a fair, productive, and, balanced regulatory system; and transparency in economic, financial, legislative, and regulatory systems. The country should also liberalize capital account transactions. To do so successfully, and minimize risks associated with foreign investors, capital account liberalization must be properly sequenced. The chief danger is removing most restrictions on capital account transactions, before addressing major problems in the domestic financial system, and hence risking a crisis. Typical major problems include shaky, inconsistent macroeconomic management; severe asymmetric information problems (such as inadequate accounting, auditing, and disclosure practices) in the financial, and corporate sectors; implicit government guarantees; and inadequate prudential supervision, and regulation of domestic financial markets, and institutions. Essential infrastructure must be developed if domestic debt instruments are to be opened to international portfolio investment. Developing countries should implement well-synchronized settlement, and depository arrangements. The risks from short-term debt - which could threaten financial stability - are best through sound financial management, and prudential regulation. A case could de made for additional policy measures aimed at curbing over-reliance on short-term debt. (Chile, Colombia, and Israel, for example, have adopted measures to influence the level, and composition of portfolio capital inflows). Arguably, liberalization of trade in financial services is integral to full liberalization of capital markets. Foreign firms operating in a domestic market may transfer useful technology, and know-how. Concern that hedge funds can dominate, or manipulate markets, can be dealt with through measures to strengthen supervision, regulation, and market transparency - as well as by strengthening reporting requirements for larger traders, and positions. The ability of hedge funds, and other foreign investors to take positions in domestic financial markets, could also be limited to: a) Taxing short-term capital flows (as Chile does). b) requiring banks, and brokers to raise margin, and collateral requirements. c) Limiting financial institutions; ability to provide the domestic credit needed to short the currency, and their ability to loan the securities needed to short equity, and fixed-income markets.